Mrs. Morris and the ghost of Christmas past - Wilton, Traci (Wilton, Traci. Salem B&B mystery, 2020)
"Charlene's parents are in town for Christmas, and her mother is driving her up a tree. Her bed-and-breakfast's resident ghost, Jack, isn't fond of her either--and he's showing it with some haunting high jinks. But when Charlene takes her mom and dad out for dinner, the less-than-seasonal spirits take a deadly turn. David Baldwin has just won a fortune in the lottery--and it adds a lot of drama to the charity auction he's hosting at his restaurant. When he caps off the evening by playing Santa and handing out checks to some of the attendees, the mood shifts . . . and Charlene observes mysterious tensions between David and his flashy, bleached-blonde wife, his neglected teenage son from a previous marriage, and his hostile business partner, among others. And they're only a few on the long list of potential suspects when David runs into the road and is mowed down by a fleeing motorist. Now it looks like it's going to be homicide for the holidays . . ." --